Cell-Specific Detection of miR-375 Downregulation for Predicting the Prognosis of Esophageal Squamous Cell Carcinoma by miRNA In Situ Hybridization - Li, Jiangchao; Li, Xiaodong; Li, Yan; Yang, Hong; Wang, Lijing; Qin, Yanru; Liu, Haibo; Fu, Li; Guan, Xin-Yuan (PloS one, 2013)
MicroRNAs (miRNAs) play important roles in the regulation of genes associated with cancer development and progression. By the more deeply characterization of miRNAs' effect in cancer development, it requires a useful tool to investigate expression and distribution of a miRNA in cancer cells and tissues. To fulfill this application demand, we developed a miRNA in situ hybridization (MISH) approach using the 2'-Fluoro modified miRNA probe in combination with enzyme-labeled fluorescence (ELF) signal amplification approach. MISH was used to study expression of miR-375 in esophageal squamous cell carcinoma (ESCC) cell lines and tissues using a tissue microarray (TMA) containing 300 cases. The results showed that our MISH approach is a practical way to detect expression and distribution of a tested miRNA in both cultured cells and archive tissue sections. MISH results also showed that miR-375 was frequently downregulated in ESCCs, which was significantly associated with advanced clinical stage (p = 0.003) tumor metastasis (p = 0.04) and poor outcome (p = 0.04) of ESCC. Moreover, the accuracy of MISH results could be confirmed by QRT-PCR. Our results demonstrated that MISH is a useful and reliable tool to study miRNA expression in solid tumors. Downregulation of miR-375 can be used as a biomarker to predict the outcome of ESCC.